Tourism Sector and Economic Growth on Employment Absorption in Central Java - Zainab Azizah; Sri Runtiningsih; M. Andi Auliya Hakim (Efficient: Indonesian Journal of Development Economics, 2025)
The tourism sector is one of the main drivers of the economy in Indonesia, contributing to GDP, job creation, and regional development. Central Java Province, with a significant contribution to employment absorption and economic growth from the tourism sector, has great potential in terms of nature, culture, and history.  This study aims to analyze the tourism and economic growth on employment absorption in the tourism sector of Central Java. Quantitative analysis with panel data from 35 regencies/cities in Central Java from 2019-2023 uses panel data regression. Data was obtained from BPS and Department of Youth, Sport, and Tourism of Central Java.. The findings show that the F-statistic value is 4.66 with a probability value of 0.011 (<0.05), indicating that the independent variables significantly affect employment absorption. However, of the two independent variables, only the tourism sector has a positive and significant effect. Strengthening the tourism sector through destination promotion and infrastructure is necessary to support economic recovery post-pandemic.